Losing sight of the trees for the forest? Attention allocation and anomalies. Issue 11 (1st November 2016) - Jacobs, Heiko; Weber, Martin
Abstract : This paper tests asset pricing implications of the investor attention shift hypothesis proposed in theoretical work. We create a novel proxy for the dynamics of inattention towards firm-specific information and explore its impact on prominent return anomalies. As hypothesized and with all else equal, the proxy positively predicts the post-earnings announcement drift as well as the profitability of pairs trading, and negatively predicts the success of momentum strategies. Taken together, our findings highlight the importance of time-varying investor attention allocation for the price discovery process.